Growth, development and chemical composition of bush tea (Athrixia Phylicoides L.) as affected by seasonal nitrogen, phosphorus, and potassium nutrition - Soundy, Puffy (University of Pretoria, 2013)
Thesis (PhD (Plant Production and Soil Science))--University of Pretoria, 2006.